ESTUDO DA DEPENDÊNCIA COMPOSICIONAL COM AS PROPRIEDADES TÉRMICAS E ESPECTROSCÓPICAS DO SISTEMA TeO2-Li2O-BaO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
In this work were studied the tellurite glasses of the glass system (100-x-y)TeO2-yLi2O-xBaO obtained by melt quenching method and characterized by techniques X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), Raman Spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), UV-Vis Spectroscopy, linear refractive index and density measurements. The results of DRX measurements allowed classifying the samples with a standard characteristic diffraction amorphous structures. The DSC results show that the samples located close to the center of the glass-forming region have the highest values for the thermal stability, these being greater than 100 °C. Results of Raman spectroscopy show that there is a decrease in the connectivity of the network glass formed and of the TeO4 units with decreasing amount of tellurium. The units of TeO3+1 show an increase while for TeO3 units there is not a well defined behavior. The FTIR results show a decrease in TeO4 units and increase in TeO3 units with decreasing amount of tellurium. The Band Gap (Eg) energy values obtained are in agreement with those found in the literature for tellurite glasses. The results also indicate that electronic transitions that occur are of the type permitted indirect, still being observed an increase in Eg values as tellurium replaced. The structural changes create Non Bridging Oxygen (NBO), but the connection between the NBO and Te atoms is weak, which do not influence in Eg behavior. This influence starts to be strong above a certain value of BaO content (which depends on the Li2O content). While these values to the energy band gap increase, the values of the linear refractive index decreases, agreeing with what is presented in the literature. For polarizability ion oxide, only the samples with 5% Li2O shows behavior consistent with what is reported in the literature, inversely proportional to the Band Gap values and proportional to the refractive index.
Keywords: vidros teluretos; energia de Band Gap; Raman; estabilidade térmica; tellurite glasses; Band Gap energy; Raman; thermal stability.; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA